IMPLEMENTASI DIGITAL MARKETING DAN STRATEGI PEMASARAN DALAM PENGEMBANGAN UMKM PADA DESTINASI WISATA POHON SERIBU SASAK RANAH PASISIE - Asraf, Asraf; Yuliza, Mai; Erdawati, Erdawati; Utami, Sri (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2024)
This research aims to find the influence of digital marketing and marketing strategies on the development of culinary businesses using a quantitative study approach. The research population was 60, who were all culinary business people at this tourist attraction. Measurement of research variables was carried out using a questionnaire with answers based on a Likert scale, then the data was processed using the SPSS and Smart-PLS applications. Regression testing shows that digital marketing has no significant effect while marketing strategy has a positive and significant effect. The implications of this research show that the use of digital marketing in a short period of time has not had an impact on business development so it needs to be carried out continuously over a long period of time. The right marketing strategy can support business development so it needs to continue to be innovated with new innovations.